Evaluating User Experience Elements on a Web System to Support Physiotherapeutic Treatment - Silvério, Miriéle dos Santos; Santos, Luciana Brasil Rebelo dos (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2019)
The trend of process automation has revealed the need of research to include different profile of people to the digital solutions in progress. Therefore, this article is the result of applying aspects of Human-Computer Interaction (HCI) theoretical reference on the developed information system, directed to a physiotherapy clinics. Based on the study of the operation in a specific clinic, we built a web platform that allows the practice of common activities, which used to be done on paper. Hence, the system was evaluated in the production environment to provide the fault finding, referred to the software usability principles, through the user experience. In all, 4 patients and 2 clinic staff participated in the experiment.